2021
DOI: 10.1021/acssuschemeng.0c09146
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Converting Carbon Dioxide to Syngas over Intermetallic AuCu Catalysts

Abstract: Electroreduction of carbon dioxide (CO2) is attractive for efficiently recycling excessive CO2 to value-added feedstocks. However, their efficiency and selectivity strongly rely on the electrocatalysts. Herein, we report intermetallic AuCu catalysts for the selective and efficient CO2 conversion to syngas. Particularly, the ordered AuCu intermetallic catalyst achieves a high faradic efficiency of 75% with a partial current density of 78.3 mA cm–2 at −0.6 V vs reversible hydrogen electrode (RHE) for producing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…The ones of Pd 0 could be contributed to by the metallic Pd in the PdCu 3 alloy. For the Cu 2p XPS spectrum, the two peaks at the binding energies of 932.4 and 951.3 eV (Figure S6b) could be assigned to Cu 2p 3/2 and Cu 2p 1/2 , respectively. Impressively, by comparing PdCu 3 /NC with Pd/NC and Cu/NC (Figures a,b and S7), it can be found that Pd 3d 5/2 is shifted to the higher binding energy, while Cu 2p 3/2 is shifted to the lower energy. These shifts might be attributed to the complex electronic effects brought about by the formation of Pd–Cu bonds between Pd and Cu.…”
Section: Resultsmentioning
confidence: 97%
“…The ones of Pd 0 could be contributed to by the metallic Pd in the PdCu 3 alloy. For the Cu 2p XPS spectrum, the two peaks at the binding energies of 932.4 and 951.3 eV (Figure S6b) could be assigned to Cu 2p 3/2 and Cu 2p 1/2 , respectively. Impressively, by comparing PdCu 3 /NC with Pd/NC and Cu/NC (Figures a,b and S7), it can be found that Pd 3d 5/2 is shifted to the higher binding energy, while Cu 2p 3/2 is shifted to the lower energy. These shifts might be attributed to the complex electronic effects brought about by the formation of Pd–Cu bonds between Pd and Cu.…”
Section: Resultsmentioning
confidence: 97%
“…They illustrated that CO selectivity was increased with the reduction in N coordination with Ni and the HER could be promoted by unsaturated Fe–Nx sites, thus the ratio of CO and H 2 could be adjusted. Similarly, Xia and co-workers designed an AuCu catalyst that could also convert CO 2 into syngas in a range of −0.4 and −1.1 V vs RHE . Although much progress has been realized in synthesized syngas, some key issues remain.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Xia and co-workers designed an AuCu catalyst that could also convert CO 2 into syngas in a range of −0.4 and −1.1 V vs RHE. 25 Although much progress has been realized in synthesized syngas, some key issues remain. Firstly, lots of catalysts used to produce syngas are composed of noble metals (like Pd, Au, Ag, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the AuCu IMC was prepared for the highly selective and efficient conversion of CO 2 to syngas. 14 In the H-type cell, the AuCu IMC has a maximum CO Faraday efficiency (FE) of 86% and a CO partial current density of 6.4 mA cm −2 at −0.9 V. Furthermore, in the flow tank configuration, the CO partial current density reaches more than 78 mA cm −2 at −0.6 V. The excellent performance is attributed to the strong electron interaction between Au and Cu atoms, that is, the transfer of electrons from Au to Cu. The transfer of electrons leads to the enhanced adsorption energy of the key intermediate CO 2 *, further improving the reactivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%